Hemodialysis Access : Fundamentals and Advanced Management - Shalhub, Sherene; Dua, Anahita; Shin, Susanna (Springer International Publishing : Imprint: Springer, 2017)
This comprehensive reference on the fundamentals of hemodialysis access creation and advanced management for maintenance is designed to meet the needs of all surgeons and physicians responsible for the treatment and care of patients undergoing dialysis. The book opens by discussing every aspect of dialysis access planning, including selection of the right access for the individual patient and access strategies. Hemodialysis access techniques, from the most basic to the most complex and unconventional, are then described step by step, and guidance is provided on follow-up and taking the newly created access to maturation so that it can be used for hemodialysis. Detailed attention is also devoted to the challenging management of specific complications of dialysis access surgery, including failing hemodialysis access. The closing section provides an understanding of the hemodialysis machine and the hemodialysis process itself, thus serving as a bridge between what nephrologists see and what surgeons manage. The book includes a wealth of informative, high-quality images and illustrations, and the authors are prominent, highly respected vascular surgeons, transplant surgeons, general surgeons, nephrologists, and interventional radiologists from across the United States.
Keywords: Medicine.; Nephrology.; Surgery.; Surgical transplantation.; Vascular surgery.; elektronické knihy; electronic books